Otimização da extração de óleo por solventes e secagem em espécies vegetais com potencial energético - Fornasari, Carlos Henrique (2014)
Extractors and the methodologies target the highest oil extraction . Following this context, this study aimed to compare the efficiency of solvents , hexane and petroleum ether , and the moisture content of the grains in the extraction of peanut oil ( Arachis hypogaea L. ) , sunflower ( Helianthus annuus L. ) , soybean ( Glycine max ) , crambe ( crambe abyssinica ) and canola ( Brassica napus L. ) . The experimental design used was completely randomized , factorial 5 x 2 x 2 with four replicates totaling 80 experimental units . The content of each kind of oil has been reported as well as the effect that grain moisture and solvents have on the yield of oil. The results obtained were subjected to analysis of variance and the interaction between the factors and their means were compared using Tukey's test at 1 and 5 % probability of error , with the statistical tool Assistat ® version 7.5 beta . When F was significant interaction was performed unfolding . There was interaction between moisture solvent, ie , in different species , solvents and variations in humidity behaved differently in relation to the yield of oil extracted from the seeds . The extraction of oil with moisture near zero using hexane as solvent showed significant increase on the yield of canola oil when extracted with relative humidity near zero with petroleum ether . Gave the lowest oil when applied petroleum ether with natural grain moisture of 9.44 % . Regarding crambe , there was no significant difference in oil yield when using hexane or petroleum ether with humidity close to zero , however, with natural moisture in the grain of 7.75 % , using hexane there was an increase in the yield of oil 11.95% when compared to extraction with moisture close to zero using the same solvent. For peanuts is observed that there was no significant difference in oil yield when using hexane or petroleum ether with humidity close to zero , however, showed a significant difference in oil yield when using petroleum ether as solvent with natural moisture 6.69 % compared to extraction with hexane with the same natural moisture , an increase of 8 , 85 % . As sunflower , there was no significant difference compared to the solvents used and there was no interaction between moisture solvent in oil yield, however , a significant difference in extraction between moisture near zero and natural moisture in the grain of 6.83 %, an increase in yield of 6.89 % when oil extraction occurred with grain moisture close to zero . There was no significant difference in the yield of soybean oil as a function of solvent and moisture in the grain used in the extraction . In this study , the solvents used in extraction and moisture changes significantly influenced the extraction efficiency , according to the characteristics and interactions in the matrices analyzed .